Interpersonal Communication Between Parents and Children in Households in Bontomate'ne Village, Maros Regency, South Sulawesi - Syam, Azizah Lutfiah; Akbar, Muh.; Arianto, Arianto (International Journal on Advanced Science, Education, and Religion, 2025)
This research focuses on how communication between parents and children occurs in families in Bontomate'ne Village, Maros. The researcher wants to deeply understand the communication process that takes place, as well as what obstacles parents face in communicating with their children. To achieve this goal, researchers used a qualitative approach with observation, interviews, and documentation methods. The data obtained was then analyzed in depth to describe the situation of communication in families in the village. The results showed that communication between parents and children in Bontomate'ne Village generally involves verbal and non-verbal communication. Parents tend to use a non-coercive approach and try to instill religious, social and moral values ​​in their children. This study also identified several barriers that parents often face in communicating with their children. These obstacles include difficulties in understanding children, the influence of a less supportive surrounding environment, and children's emotional immaturity.